Tenascins Interfere With Remyelination in an Ex Vivo Cerebellar Explant Model of Demyelination - Bauch, Juliane; Ort, Sina Vom; Ulc, Annika; Faissner, Andreas (Frontiers in Cell and Developmental Biology, 2022)
Oligodendrocytes form myelin membranes and thereby secure the insulation of axons and the rapid conduction of action potentials. Diseases such as multiple sclerosis highlight the importance of this glial cell population for brain function. In the adult brain, efficient remyelination following the damage to oligodendrocytes is compromised. Myelination is characterized by proliferation, migration, and proper integration of oligodendrocyte precursor cells (OPCs). These processes are amongst others controlled by proteins of the extracellular matrix (ECM). As a prominent representative ECM molecule, tenascin-C (Tnc) exerts an inhibitory effect on the migration and differentiation of OPCs. The structurally similar paralogue tenascin-R (Tnr) is known to promote the differentiation of oligodendrocytes. The model of lysolecithin induced demyelination of cerebellar slice cultures represents an important tool for the analysis of the remyelination process. Ex vivo cerebellar explant cultures of Tnc-/- and Tnr-/--mouse lines displayed enhanced remyelination by forming thicker myelin membranes upon exposure to lysolecithine. The inhibitory effect of tenascins on remyelination could be confirmed when demyelinated wild-type control cultures were exposed to purified Tnc or Tnr protein. In that approach, the remyelination efficiency decreased in a dose-dependent manner with increasing concentrations of ECM molecules added. In order to examine potential roles in a complex in vivo environment, we successfully established cuprizone-based acute demyelination to analyze the remyelination behavior after cuprizone withdrawal in 129/SV-, Tnc-/- and Tnr-/--mice. In addition, we documented by immunohistochemistry in the cuprizone model the expression of chondroitin sulfate proteoglycans that are inhibitory for the differentiation of OPCs. In conclusion, inhibitory properties of Tnc and Tnr for myelin membrane formation could be demonstrated by using an ex vivo approach.